Clinical characteristics and short-term outcomes of patients with critical acute pulmonary embolism requiring extracorporeal membrane oxygenation: from the COMMAND VTE Registry-2 - Kensuke Takabayashi; Yugo Yamashita; Takeshi Morimoto; Ryuki Chatani; Kazuhisa Kaneda; Yuji Nishimoto; Nobutaka Ikeda; Yohei Kobayashi; Satoshi Ikeda; Kitae Kim; Moriaki Inoko; Toru Takase; et al. (Journal of Intensive Care)
Abstract Background Extracorporeal membrane oxygenation (ECMO) might be required as a treatment option in patients with critical pulmonary embolism (PE). However, the clinical features and outcomes of the use of ECMO for critical acute PE are still limited. The present study aimed to clarify the clinical characteristics, management strategies and outcomes of patients with acute PE requiring ECMO in the current era using data from a large-scale observational database. Methods We analyzed the data of the COMMAND VTE Registry-2: a physician-initiated, multicenter, retrospective cohort study enrolling consecutive patients with acute symptomatic venous thromboembolism (VTE). Among 2035 patients with acute symptomatic PE, there were 76 patients (3.7%) requiring ECMO. Results Overall, the mean age was 58.4 years, and 34 patients (44.7%) were men. Cardiac arrest or circulatory collapse at diagnosis was reported in 67 patients (88.2%). The 30-day incidence of all-cause death was 30.3%, which were all PE-related deaths. The 30-day incidence of major bleeding was 54.0%, and the vast majority of bleedings were procedure site-related bleeding events and surgery-related bleeding (22.4%). The 30-day incidence of all-cause death was 6.3% in 16 patients with surgical intervention, 43.8% in 16 patients with catheter intervention, 25.0% in 16 patients with thrombolytic therapy, and 39.3% in 28 patients with anticoagulation only. Conclusions The current large real-world VTE registry in Japan revealed clinical features and outcomes of critical acute PE requiring ECMO in the current era, which suggested several unmet needs for future clinical trials.